The role of implicit learning in logo substitution. Issue 5 (12th August 2019) - Ohme, Rafal; Boshoff, Christo
Abstract : Purpose: Some marketers have challenged psychologists' contention that human beings can only learn by using conscious effort. They argue that advertising can be effective at low levels of (or even no) attention. Also, despite the absence of (or low levels of) consciousness, these subconscious responses can be linked to brands. The purpose of this study is to investigate the impact of implicit learning in the context of logo substitution – an image that may not look like the original logo, and may not even be consciously associated with the original brand or its logo. Design/methodology/approach: Data were collected by means of two quasi-experimental studies. Findings: The results suggest that, thanks to implicit learning, logo substitution can be effective. Research limitations/implications: One limitation was that data were collected from two relatively small convenience samples. Practical implications: Logo substitution can be of value when a company faces a situation when advertising is banned or restricted, when the target market is saturated with marketing stimuli (clutter) and when there is a risk that aggressive advertising can lead to psychological reactance. The purpose of logo substitution would then be to unobtrusively activate mental representations closely related to the original logo. Originality/value: The central contribution of this study is that it demonstrates how the principles of implicit social cognition, implicit learning and logo substitution can be used by marketers to overcome the undesirable and even adverse advertising circumstances they sometimes face.